Medical Students' Knowledge and Attitudes Toward Female Sex Workers and Their Occupational Risk Factors - Jenna T. Nakagawa; Muge Akpinar-Elci (University Library System, University of Pittsburgh, 2014)
Background: The tendency for female sex workers to seek health care is highly influenced by physician attitudes and behavior. By identifying medical students' attitudes toward female sex workers and assessing their knowledge of barriers to seeking care, we can focus medical training and advocacy efforts to increase access to care and improve public health outcomes. Methods: In this cross-sectional study, medical students from various countries were invited to participate in an online survey with close-ended questions and Likert scale statements. Responses were quantified and knowledge and attitude scores were assigned based on knowledge of barriers to seeking care and agreement with positive and negative attitude statements. Results: A total of 292 medical students from 56 countries completed the survey, of whom 98.3% agreed that it will be their job to provide treatment to patients regardless of occupation. Self-identified religious students conveyed more negative attitudes toward female sex workers compared to those who did not identify themselves as religious (p<0.001). Students intending to practice in countries where prostitution is legal conveyed more positive attitudes compared to those intending to practice in countries where prostitution is illegal (p<0.001). Conclusion: Medical students largely agreed on the importance of providing care to female sex workers as a vulnerable group. In addition to addressing knowledge gaps in medical education, more localized studies are needed to understand the religious and legal influences on attitudes toward female sex workers. Such information can help focus the efforts in both medical education and communication training to achieve the desired behavioral impacts, reconciling the future generations of health care providers with the needs of female sex workers.